Efecto de dosis de nitrógeno y micorrizas en el rendimiento y composición del grano de maíz blanco variedad INIAP-103 en condiciones del sector La Argelia de la ciudad de Loja - Macas Camacho, Erika Lizbeth (2022)
Corn (Zea mays L.) is one of the most important cereals because it is one of the five most consumed crops around the world, due to the different uses that it has, such as human and animal food, and fermented for some industrial products. In Ecuador, this grain is the main element of the daily diet of people, especially in the Sierra region; however, the cultivation of white corn in the country has low yields. Generally, in most of the Andean region of the country, corn is planted in monocultures, it is a practice that ends up depleting soil nutrients, causing a decreasing in yields in each new crop cycle. In addition, when the exact dose of fertilizer required by the crop is not known, there is a tendency to apply large amounts of fertilizer, especially nitrogen, but not all of it is used by the plants and most of it gets lost either by volatilization in the form of ammonium, denitrification and/or leaching in the form of nitrates. An alternative to contribute to increase the yield and composition of corn grain is to use environmentally friendly alternatives, such as the use of mycorrhizae, so this is the reason, in this research, different doses of nitrogen (100-50-0 %) and mycorrhizae (0-100-200 %) were evaluated on the white corn variety INIAP - 103 "Misqui Sara" (Nutritious corn), under an agronomic management typical of the Sierra region. For this purpose, a white corn crop was established in the sector of La Argelia city of Loja, in southern Ecuador, with a duration of 8 months, planted at a density of 62500 plants ha-1 (1 seed per stroke every 0.2 m and 0.8 m between rows), under a completely randomized design (CRD), with 9 treatments. Plant height, stem diameter, number of leaves, absolute growth rate (AGR), relative growth rate (RGR), leaf area, leaf area index (LAI), fresh and dry biomass, yield, percentage of nitrogen and crude protein in the grain were evaluated in each treatment. Among the results, treatment 2 (100 % N and 100 % mycorrhizae) stood out in variables such as height with 243.4 cm, diameter 3.30 cm, biomass and yield 8.0 t ha-1, while the total number of leaves was similar in all treatments. In addition, treatment 8 (0 % N and 100 % mycorrhizae) has more relevance in variables such as leaf area 0.38 m2, IAF 2.39, as for the percentage of nitrogen 1.56% and crude protein 10.27% was obtained by treatment 6 (50 % N and 200 % mycorrhizae). The results of this research highlight the effect of different doses of nitrogen and mycorrhizae, since yield can be improved in white corn varieties adapted to the Sierra region. Key words: nitrogen, mycorrhizae, crude protein.